PENERAPAN KAIDAH “AL-IJTIHAD LA YANQUD BI AL-IJTIHAD” DALAM KASUS FIKIH - Andi Muh. Taqiyuddin BN; Ahmad Arief; Marzuki Umar; Misbahuddin Misbahuddin; Sabri Samin (Fakultas Syariah (Syari'ah Faculty ), 2022)
This research is qualitative, the type of research is library research and uses a normative juridical approach. The data collection method used was a literature study. The results showed that; 1) The meaning of the rule (Ijtihad Does Not Cancel Other Ijtihad), namely the rule (Ijtihad Does Not Cancel Other Ijtihad) means that ijtihad cannot produce a product that has been implemented at a certain time and place, it cancels the legal product of an ijtihad result. at one time and another. 2) The validity of the principle (Ijtihad does not cancel other Ijtihad), namely the honesty of this principle can be seen from the existence of the arguments that legalize it. Starting from the hadith until then the consent of a friend, as we have stated, this can be noticed from a caliph 'Umar who did not annul or cancel his predecessor's opinion or ijtihad, namely Abu Bakr. 3) Implementation of the rule (Ijtihad does not cancel other Ijtihad), which can be seen from the examples in the literature that discuss al-Qawa'id al-Fiqhiyyah. This rule is valid as long as it does not violate or contradict the nas, consent, qiyas jaliy, the words of the 4 schools, and it is clear that the judge's error is the result of the law, cause, or method. Also, ijtihad must be equally strong, it cannot be just one of them, and finally, that the implementation of ijtihad has been legitimized by Fatwa or Qa ataupunā. So the implementation of this rule can be noticed in existing examples and this rule is not always able to be implemented or implemented, because several things have been mentioned regarding the exceptions regarding this rule.